Mengedukasi Petani Anggrek: Upaya Peningkatan Kesadaran Lingkungan di Sektor Pertanian Petani Mitra DD Orchid Nursery - Nugroho, Taufik Rizal Dwi Adi; Agustin, Vegyta Irna; Mawardani, Eka Istara; Ulfa, Maria; Saubari, Fahmi (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This activity aims to provide an in-depth understanding of sanitation to DD Orchid Nursery partner farmers in Batu Malang City. The method used is a partnership-collaboration approach with two stages: preparation of outreach and implementation of activities. The results of the implementation of the activity showed a positive impact in the form of increasing farmers' awareness of the importance of environmental cleanliness around their orchid gardens. This has a positive impact on the health of the orchids and the workers. With this approach, partner farmers have succeeded in understanding how important it is to maintain a clean environment to support healthy orchid growth. It is hoped that this awareness will bring positive changes in their agricultural practices and increase orchid yields. Through this collaborative partnership, efforts to improve sanitation in the orchid cultivation sector will become more focused and targeted, strengthening the company's contribution to supporting sustainable agricultural practices.